Lithium Improves Survival of PC12 Pheochromocytoma Cells in High-Density Cultures and after Exposure to Toxic Compounds. (19th January 2014) - Fabrizi, Cinzia; De Vito, Stefania; Somma, Francesca; Pompili, Elena; Catizone, Angela; Leone, Stefano; Lenzi, Paola; Fornai, Francesco; Fumagalli, Lorenzo
Abstract : Autophagy is an evolutionary conserved mechanism that allows for the degradation of long-lived proteins and entire organelles which are driven to lysosomes for digestion. Different kinds of stressful conditions such as starvation are able to induce autophagy. Lithium and rapamycin are potent autophagy inducers with different molecular targets. Lithium stimulates autophagy by decreasing the intracellular myo-inositol-1, 4, 5-triphosphate levels, while rapamycin acts through the inhibition of the mammalian target of rapamycin (mTOR). The correlation between autophagy and cell death is still a matter of debate especially in transformed cells. In fact, the execution of autophagy can protect cells from death by promptly removing damaged organelles such as mitochondria. Nevertheless, an excessive use of the autophagic machinery can drive cells to death via a sort of self-cannibalism. Our data show that lithium (used within its therapeutic window) stimulates the overgrowth of the rat Pheochromocytoma cell line PC12. Besides, lithium and rapamycin protect PC12 cells from toxic compounds such as thapsigargin and trimethyltin. Taken together these data indicate that pharmacological activation of autophagy allows for the survival of Pheochromocytoma cells in stressful conditions such as high-density cultures and exposure to toxins.